Aspects of the revegetation of mountain fynbos vegetation of the south western Cape, South Africa - Romoff, Natalie (Department of Biological Sciences, 2016)
The revegetation of severely, disturbed areas using indigenous vegetation forms the topic of this thesis. Mountain Fynbos was chosen for the study because of its importance as a unique vegetation-type worthy of conservation. Unfortunately, this vegetation faces long-term threats associated with escalating development pressures, which include the demand for improved infrastructures. These factors are discussed and a process is developed for using indigenous vegetation to revegetate severely disturbed areas. This use of indigenous vegetation represents a significant and innovative move away from the traditional use of commercially available grasses in South Africa. Fynbos is adapted to periodic droughts and nutrient poor soils and as such has practical advantages over artificial plant covers in terms of its low maintenance requirements for long term establishment. Theoretical perspectives of disturbance and succession are contrasted with the requirements for revegetation as observed in the field.